2020
DOI: 10.3389/fvets.2020.00564
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Salmonella Spread in Broiler Production: Identifying Determinants and Control Strategies

Abstract: The presence of Salmonella spp. in broiler production is a food safety concern as the bacterium can be transmitted to humans via contaminated meat and derived products. Salmonella detection in litter at the pre-slaughter period has been linked to increased odds of contaminated broiler carcasses and meat derived products. To determine risk factors related to farm and broiler house characteristics and management practices, this study uses a unique longitudinal data set from a Brazilian integrated broiler enterpr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 47 publications
1
9
0
Order By: Relevance
“…On the other hand, the MBC for S. enteritidis and S. gallinarum was 10.71 μg/mL (26.02 μM). The findings suggested that the α-mangostin was efficient in killing and inhibiting the growth of common bacteria found in broilers [ 35 ]. The antimicrobial effect of α-mangostin on gram-positive and gram-negative bacteria has been reported.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the MBC for S. enteritidis and S. gallinarum was 10.71 μg/mL (26.02 μM). The findings suggested that the α-mangostin was efficient in killing and inhibiting the growth of common bacteria found in broilers [ 35 ]. The antimicrobial effect of α-mangostin on gram-positive and gram-negative bacteria has been reported.…”
Section: Resultsmentioning
confidence: 99%
“…which is a natural inhabitant of the gastrointestinal tract of birds. The infection of the bacteria in broilers could cause foodborne disease due to the transmission to humans through contaminated meat and derived products [ 35 ]. Thus, the infection is highly concerning.…”
Section: Resultsmentioning
confidence: 99%
“…Litter microbiome analyses have demonstrated associations between the physicochemical characteristics of the litter, the abundance of specific taxa, the associated ability to isolate foodborne pathogens such as Salmonella and Campylobacter , and the litter influence on gut colonization [ 50 , 51 , 52 ]. Specifically, for Salmonella , Machado and Hagerman [ 53 ] reported decreasing odds for the probability of detecting Salmonella in litter prior to harvest with successive litter reuses up to six rearing cycles, after which, however, the odds began to increase. Conversely, in another study, Salmonella detections in recycled litter continued to decrease with up to 14 reuse cycles [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…The poultry industry usually implements strategies of surveillance and biosecurity at international, national, and farm levels to prevent Salmonella spread [ 119 , 120 , 121 , 122 ]. Among the health management protocols, vaccination represents the most efficient and cost-effective method to reduce the impact of clinical disease, maintain herd immunity, decrease the shedding and reduce both horizontal and vertical transmission of Salmonella in poultry flocks [ 19 , 123 , 124 , 125 , 126 ].…”
Section: Non-feeding-based Strategiesmentioning
confidence: 99%